The Role of Parental Social Support in Children's Pushbike Achievement in the Sedulur Pushbike Community - Mochammad Azzam El Naisabury; Fery Darmanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the role of parental social support on children's achievement in pushbike sports in the Sedulur Pushbike Community in Tegal City. This study uses a descriptive qualitative approach involving parents, children participating in pushbike activities, and community coaches as participants. Data were collected through in-depth interviews, observations, documentation, and online questionnaires distributed to 15 respondents. Interview data was analyzed using NVivo, while descriptive statistical analysis was conducted using SPSS. The findings revealed that parental social support plays an important role in improving children's achievement in pushbike sports. This support includes emotional support in the form of motivation and mentoring, instrumental support through the provision of facilities and competition costs, information support through communication with coaches, and assessment support through praise and encouragement. This support contributes to increased motivation, confidence, courage, training consistency, and motor and social development of children. In addition, active parental involvement creates a positive social environment that supports children's development and achievement in pushbike activities. Therefore, parental social support can be considered an important factor in supporting a child's success in early childhood sports.